Comparison of various body fat indices in early and mid-adolescents of South India: School-based cross-sectional study - Selvi, Ayyavoo; Naaraayan, Sridevi A; Priyadharishini, Dorairaj; Begum, N Shajathi (Indian Journal of Child Health, 2018)
Background: The most important bottleneck in the management of obesity is a lack of a gold standard measuring tool. Although body mass index (BMI) is the most commonly used index to identify obesity, other indices such as waist circumference and skinfold thickness are more specific in measuring fatness. Objective: The objective of the study was to determine the agreement between BMI, waist circumference, and triceps skinfold thickness (TSFT) against body fat percentage calculated using 7-site skinfold thickness in South Indian adolescents. Methods: This cross-sectional study was performed in selected government-run schools in Chennai from May 2016 to October 2016. Schoolchildren of age 10–16 years without any medical illness which are known to cause discordant body proportions were included in the study. Sample size was fixed at 700. Date of birth, gender, and the anthropometric parameters, namely, height, weight, waist circumference, and skinfold thickness at triceps, chest, axilla, abdomen, thigh, subscapular, and suprailiac regions were measured by standard procedure and noted. Body fat percentage was calculated from 7-site skinfold thickness using Jackson-Pollock formula. Participants were classified as obese and non-obese based on BMI, waist circumference, TSFT, and body fat percentage using appropriate standards. Agreement between various indices was determined using Cohen’s kappa statistic. Results: BMI, waist circumference, and TSFT showed moderate agreement with body fat percentage calculated from 7-site skinfold measurement. BMI and TSFT showed substantial agreement (k=0.608 for BMI and k=648 for TSFT) with body fat percentage in girls and only fair agreement (k=0.366 for BMI and k=0.291 for TSFT) in boys. Waist circumference showed moderate agreement with body fat percentage in boys (k=0.523) and girls (k=0.575). Conclusion: BMI, waist circumference, and TSFT show moderate agreement with body fat percentage calculated from 7-site skinfold measurement in South Indian adolescents. Measurement of waist circumference is recommended to classify an adolescent as obese, especially boys.